2023
DOI: 10.1007/s00227-023-04228-x
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviour of black guillemots at three Norwegian sites during the breeding season

Abstract: The intensification of coastal development poses potential threats for coastal seabirds, and understanding their habitat use is a key factor to guide conservation and management. In sub-arctic areas, black guillemots (Cepphus grylle) use coastal habitats year-round, which makes them vulnerable to the increasing human activities in these areas. In mainland Norway, one of the species’ strongholds, black guillemots are red-listed after substantial population declines. However, their fine-scale foraging behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…We found that even with a moderate fishing restriction of more than 30 m depth in place, up to 90% of the black guillemot bycatch could be prevented, which may be sufficient to arrest the population decline observed in the last decades. In the light of our findings, a recent study on the foraging behaviour of black guillemots in Norway highlights the importance of shallow marine areas (less than 50 m) for this species, with foraging probability declining with increasing water depth [ 46 ].…”
Section: Discussionmentioning
confidence: 85%
“…We found that even with a moderate fishing restriction of more than 30 m depth in place, up to 90% of the black guillemot bycatch could be prevented, which may be sufficient to arrest the population decline observed in the last decades. In the light of our findings, a recent study on the foraging behaviour of black guillemots in Norway highlights the importance of shallow marine areas (less than 50 m) for this species, with foraging probability declining with increasing water depth [ 46 ].…”
Section: Discussionmentioning
confidence: 85%